Implementasi Metode Joyfull Learning pada Pembelajaran Pendidikan Agama Islam di SMP Muhammadiyah Sukaramai 58 - Cut Putri Salsabila (EduInovasi: Journal of Basic Educational Studies, 2025)
Islamic Religious Education, commonly known as PAI, tends to be less appealing to students. This is highlighted by their lack of enthusiasm when PAI classes commence, showing passivity and minimal engagement in the learning process. Several factors contribute to this, including insufficiently trained educators, teaching methods that feel coercive, and inadequate classroom time. To address these challenges, it is essential to incorporate enjoyable methods or joyful learning approaches. This research relates to the title “Implementation of Joyful Learning Methods in Learning Islamic Religious Education in SMP Muhammadiyah Sukaramai 58.” The research employs a qualitative methodology, utilizing purposive sampling techniques. This approach focuses on narrative analysis. The data collection encompasses observations, interviews, and study of documentation. The data analysis follows Miles and Huberman's framework, which entails data condensation, data display, verification, and conclusions. To ensure data validity, triangulation techniques and sources are employed. This study arrived at the following conclusions: (1) The joyful learning method in PAI is implemented through activities such as outbound and moving classes, outdoor sessions, mind mapping, trainer training, and gameplay supported by music played over a loudspeaker, alongside employing memorization techniques based on the super memory formula. (2) Factors that support the use of joyful learning methods in PAI at SMP Muhammadiyah Sukaramai 58 include students' diminished motivation to learn, while a barrier is the educator's insufficient creativity in integrating games into teaching using the joyful learning method.